Preparation and Characterization of Chitosan-Avocado Seed Starch (KIT-PBA) Edible Film - Endang Susilowati; Ary Eny Lestari (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
Chitosan is a biopolymer that has the advantage of being able to form films that are non-toxic which has great potential to form edible films. To improve the properties of edible films in the form of antioxidants, it is necessary to add other materials such as avocado seed starch. This study aims to determine the effect of the use of avocado seed starch on mechanical properties, degree of swelling and solubility of edible film chitosan-Avocado Seed Starch (Kit-PBA). This study uses a laboratory experimental method. Steps in this study are (1) extraction of avocado seed starch; (2) Making edible film Kit-PBA (mixing chitosan and avocado seed starch), heating and neutralizing) with a ratio between chitosan: avocado seed starch are at 50:50; 60:40; 70:30; 80:20; 90:10; 100: 0; (3) Characterization of Kit-PBA are (tensile strength and elongation) edible film mechanical properties, swelling test and solubility test. The results showed that the higher the concentration of chitosan in the Kit-PBA edible film, the tensile and elongation strength values would increase while the degree of swelling and solubility would decrease.